Peran Niat Menabung dalam Memediasi Financial Literacy dan Financial Technology Terhadap Keputusan Menabung: (Studi Mahasiswa Manajemen Universitas Semarang Angkatan 2021) - Sugeng Riyanto; Adhi Widyakto (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Economic development in a country cannot be separated from economic growth, with economic growth being an indication of success or as a determinant of economic development. The people of Indonesia are increasingly having consumptive behavior and are starting to abandon positive habits that can help economic growth to increase, namely by saving. Saving behavior or saving habits are very important to be carried out by all levels of society, including students, who are a large group of people who can lead the community to move to make changes to advance Indonesia's economic growth. This study aims to examine the influence of financial literacy and financial technology on students' savings decisions with saving intention as an intervening variable (study of management students of the University of Semarang Class of 2021). This research was carried out by random sampling with certain criteria. So that the data used was 96 respondents as a research method. The sample used was 5 indicators, so the last sample in this study was 259 observations and used data analysis using the SmartPLS application tool. The results of this research prove that financial literacy has a significant positive effect on the decision to save, financial literacy has a significant positive effect on the intention to save, financial technology has a significant positive effect on the decision to save, financial technology has no significant effect on the intention to save, the intention to save has a significant positive effect on the decision to save, financial literacy indirectly has a positive effect on the decision to save through the intention to save, financial technology indirectly has no significant effect on the decision to save through the intention to save.